2015
DOI: 10.21608/jappmu.2015.52767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biologically Treated Sugar Beet Pulp on Lactating Goat Performance

Abstract: This study amid to investigate the effect of using sugar beet pulp (SBP) untreated or treated with biological treatments to replace about 30% of common concentrate feed mixture of goat diets. In vitro experiment was carried out to study the effect of control, treated and untreated SBP on nutrients disappearance. Experimental diets included T1: Concentrate feed mixture (CFM) + Berseem hay (BH) (control). T2: CFM + untreated SBP + BH. T3: CFM + SBP treated with Sacharomyces cerevisiae + BH. T4: CFM + SBP treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Similar results were obtained by Dawson and Tricarico (2002) and Marghany et al (2005) who reported that addition of live yeast culture to ruminant diet has improved fiber digestibility and stimulated cellulolytic bacteria. Also, Aziz (2014 and2015) found an increase in total and cellulolytic bacteria numbers in rumen of goats and sheep fed biologically treated SBP.…”
Section: Total Bacteria and Cellulolytic Bacteria Numbersmentioning
confidence: 93%
See 4 more Smart Citations
“…Similar results were obtained by Dawson and Tricarico (2002) and Marghany et al (2005) who reported that addition of live yeast culture to ruminant diet has improved fiber digestibility and stimulated cellulolytic bacteria. Also, Aziz (2014 and2015) found an increase in total and cellulolytic bacteria numbers in rumen of goats and sheep fed biologically treated SBP.…”
Section: Total Bacteria and Cellulolytic Bacteria Numbersmentioning
confidence: 93%
“…Also, Aboul-Fotouh et al (2013) found that treatment of OC with yeast increased digestibility coefficient and nutritive values. Aziz (2014 and2015) found an increase (P≤0.01) in digestibility coefficients, TDN, DCP and ME for sheep fed biologically treated SBP. Abdou (2017) found that sheep fed biologically treated OC recorded higher values of feed intake and improved all nutrients digestibilities, TDN and DCP than those fed control.…”
Section: Feed Intake Digestibility Coefficients and Nutritive Valuesmentioning
confidence: 94%
See 3 more Smart Citations